Dynamic ion-releasing biomaterials actively shape the microenvironment to enhance healing - Zambuzzi, Willian Fernando [UNESP]; Ferreira, Marcel Rodrigues [UNESP] (Elsevier, 2025)
Dynamic ion-releasing biomaterials have redefined the role of implantable bone devices, transitioning them from passive mechanical support to active players in tissue regeneration. These materials actively modulate the surrounding biological microenvironment by releasing bioactive ions (e.g.: calcium, phosphate, and cobalt) which dynamically interact with cells and tissues surrounding them. This interaction becomes the microenvironment highly active and accelerates bone healing, promoting osteogenesis, and enhancing osseointegration. The ions modulate key biological processes in this regard, including osteoblast adhesion, proliferation, differentiation, angiogenesis, and immune responses, as well as coupled physiological mechanisms, ensuring that the implanted biomaterials foster an optimal environment for bone regeneration. More advanced surface modifications onto materials (e.g.: nanostructuring hydroxyapatites coatings) have been shown to further boost ion release, amplifying the ability of the material to influence surrounding tissues. As a result, ion-releasing biomaterials not only improve implant integration but also accelerate the overall healing process. Looking forward, the development of smart biomaterials capable of adjusting ion release in response to environmental changes offers exciting possibilities for personalized regenerative therapies and this review provides a comprehensive understanding of how dynamic ion-releasing biomaterials actively shape the microenvironment to enhance healing, focusing on their ability to modulate biological processes such as osteogenesis and angiogenesis. By examining the latest advances in surface modifications and ion-release mechanisms, this review also aims to revise the potential of these materials to revolutionize regenerative medicine, offering knowledge to guide the development of next-generation biomaterials for improved clinical outcomes.
Keywords: Angiogenesis; Bioactive ions; Bone regeneration; Dynamic ion-releasing biomaterials; Osseointegration